Development of Webtoon non-test instrument as education media - Mery Berlian; Rian Vebrianto; Musa Thahir (Institute of Advanced Engineering and Science, 2021)
The objective of this research was to develop non-test instrument or questionnaire to measure the evaluation of the use of Webtoon among the students of Open University in Pekanbaru, Riau, Indonesia and to obtain the instrument’s validity and reliability. This research employed the Analysis, Design, Development, Implementation, Evaluation (ADDIE) instructional model. The data were collected using online questionnaire. There were 55 respondents participated in this research. The data collected were analyzed descriptively using SPSS program version 23.00 for windows. The result of the data analysis indicated that the instrument has the percentage of agreement result of 82.75% (valid) and Cronbach alpha with score 0.942 (reliable). The data proved that the instrument has very feasible. This result showed that this research and development produced Webtoon non-test instrument which is valid and reliable.